Eternal dilemma of the interplay between coexisting tuberculosis and malignancy: Clinical scenario of coexisting submandibular carcinoma with disseminated tuberculosis: A case report - Shah, Manjari; Leekha, Nitin; Gupta, Sweety; Sowmiya, S; Garg, Garima; De, Sudarsan (Asian Journal of Medical Sciences, 2016)
Tuberculosis (TB) and malignancy are two lethal diseases that cause significant morbidity and mortality in developing countries like India. Extrapulmonary tuberculosis (TB) constitutes about 15 to 20 per cent of all cases of tuberculosis with lymph nodes being the most common site of involvement.1 Malignant transformation in pleomorphic adenoma lead to carcinoma ex pleomorphic adenoma (CXPA). CXPA of the salivary glands, however, is relatively uncommon, accounting for 3.6 % of all salivary gland neoplasms and 11.7 % of all malignant salivary gland neoplasms.2 Here we report a case of carcinoma ex pleomorphic adenoma of submandibular gland which presented as a swelling in submandibular region along with generalized lymphadenopathy which mimicked widespread metastases but later on histologically showed tuberculosis. Asian Journal of Medical Sciences Vol. 7(3) 2016 115-117